Calmodulin Binding to Connexin 35: Specializations to Function as an Electrical Synapse - Jaya Aseervatham (International Journal of Molecular Sciences, 2020)
Calmodulin binding is a nearly universal property of gap junction proteins, imparting a calcium-dependent uncoupling behavior that can serve in an emergency to decouple a stressed cell from its neighbors. However, gap junctions that function as electrical synapses within networks of neurons routinely encounter large fluctuations in local cytoplasmic calcium concentration; frequent uncoupling would be impractical and counterproductive. We have studied the properties and functional consequences of calmodulin binding to the electrical synapse protein Connexin 35 (Cx35 or gjd2b), homologous to mammalian Connexin 36 (Cx36 or gjd2). We find that specializations in Cx35 calmodulin binding sites make it relatively impervious to moderately high levels of cytoplasmic calcium. Calmodulin binding to a site in the C-terminus causes uncoupling when calcium reaches low micromolar concentrations, a behavior prevented by mutations that eliminate calmodulin binding. However, milder stimuli promote calcium/calmodulin-dependent protein kinase II activity that potentiates coupling without interference from calmodulin binding. A second calmodulin binding site in the end of the Cx35 cytoplasmic loop, homologous to a calmodulin binding site present in many connexins, binds calmodulin with very low affinity and stoichiometry. Together, the calmodulin binding sites cause Cx35 to uncouple only at extreme levels of intracellular calcium.